2009
DOI: 10.1016/j.respol.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Claiming more: the Increased Voluminosity of Patent Applications and its Determinants

Abstract: The size of patent applications has doubled over the past two decades, resulting in a dramatic surge in patent offices' workload all over the world. This paper investigates the sources of this inflation in claims and pages for EPO applications. Four hypotheses are quantitatively tested: the diffusion of national drafting practices, the complexification of research activities, the emergence of new sectors, and patenting strategies. The results first reveal major differences across countries in patent drafting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(47 citation statements)
references
References 33 publications
1
41
0
5
Order By: Relevance
“…Regarding the number of claims, van Zeebroeck et al (2006a) have shown that the severe inflation in the size of patent applications at the EPO was notably due to a progressive harmonization of drafting styles toward American drafting modes, themselves largely influenced by legal changes in the US patent system. The literature on patent value has frequently used the number of claims as a proxy for the breadth or complexity of patents (Tong and Frame, 1994), suggesting -and empirically demonstrating -a positive correlation with patent value.…”
Section: Claimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the number of claims, van Zeebroeck et al (2006a) have shown that the severe inflation in the size of patent applications at the EPO was notably due to a progressive harmonization of drafting styles toward American drafting modes, themselves largely influenced by legal changes in the US patent system. The literature on patent value has frequently used the number of claims as a proxy for the breadth or complexity of patents (Tong and Frame, 1994), suggesting -and empirically demonstrating -a positive correlation with patent value.…”
Section: Claimsmentioning
confidence: 99%
“…The PCT procedure may carry applications that are clearly aimed at being widely extended worldwide and may hence be associated with a higher economic value. But it may also concern applications that were filed very early in the innovation process, at a time when the invention's market potential was still unclear (see van Zeebroeck et al, 2006a). In such a case, the patentee may have preferred to delay by an extra 18 months the time when a final decision as to whether the application is worth being extended abroad or not would have to be made, and so the application itself may be of much 12 or of very little value, if any.…”
mentioning
confidence: 99%
“…The average pendency time for examination (time between filing and grant) at the EPO was around 40.6 months in 2005 and decreasing with respect to previous years (1.9% with respect to 2004, see OECD 2009). Pending status can be associated to several factors: growing complexity and volume of applications, increasing workload at the patent office, strategic delay for request of examination (Van Zeebroeck et al, 2009;Harhoff and Wagner, 2006). Note: (S.E.)…”
mentioning
confidence: 99%
“…Quatre hypothèses peuvent être formulées pour expliquer cette évolution : l'influence de lois et pratiques nationales et leur diffusion progressive à d'autres pays sous l'effet de la globalisation des procédures de dépôt de brevets, la complexification des activités de recherche et des inventions, l'émergence de nouveaux secteurs aux normes et vocabulaires moins établis, et la construction de larges portefeuilles de brevets. Une analyse économétrique (présentée dans van Zeebroeck et al (2006)) montre que ces quatre hypothèses participent toutes à cette inflation. Toutefois, celle qui y contribue le plus significativement semble être la première, qui se traduit par des pratiques beaucoup plus volumineuses dans les pays anglo-saxons comme illustré par la Figure 2 probablement en raison de la nature du système juridique dans les pays de droit commun -qui se propagent à l'ensemble des pays industrialisés au moyen des procédures de dépôt internationales, nommément le PCT (Patent Cooperation Treaty).…”
Section: L'inflation Des Brevetsunclassified
“…La plupart des 5 indicateurs est caractérisé par des distributions très asymétriques (Griliches, 1990;Scherer and Harhoff, 2000;Silverberg and Verspagen, 2004 ;van Zeebroeck, 2007a) qui reflètent l'asymétrie dans la distribution de la valeur des brevets, laquelle compromet en tant que telle l'utilisation de comptages de brevets comme mesure de l'output des activités de R&D. Les 5 dimensions sont par ailleurs marquées par de fortes variations géographiques et sectorielles. 180% 1980 1981 1982 1983 1984 1985 1986 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 Average value of indicator (1980=100) Outre de prendre en compte les 5 grandes classes d'indicateurs basés sur les données de brevets décrits ci-dessus et la plupart des déterminants traditionnellement étudiés dans la littérature (mesures de complexité des brevets, structure de propriété des brevets, profil des déposants), l'analyse réalisée vise à évaluer de nouveaux déterminants potentiels : les stratégies de dépôt.…”
Section: Stratégies De Dépôt Et Valeur Des Brevetsunclassified